Čokoláda s obsahem sulforafanu - Soural, Ivo; Šnurkovič, Petr; Balík, Josef; Houška, Milan; Novotná, Pavla; Tříska, Jan; Vrchotová, Naděžda; Magner, Martin; Híc, Pavel; Jílek, Ladislav; Thorová, Kateřina (Výživa a potraviny, 2022)
x
Keywords: Biochemical Phenomena; Research; Chromatography, Liquid; potravinářská technologie; výzkum; lyofilizace; Food Technology; Raphanus; chromatografie kapalinová; sulforafan; Food Analysis; biochemické jevy; Brassica; sloučeniny síry; Statistics as Topic; čokoláda; zdravá strava; Diet, Healthy; statistika jako téma; analýza potravin; Chocolate; Freeze Drying; Sulfur Compounds